Risk Management in the Ghanaian Insurance Industry - Oscar, K.; Abor, J. (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to examine the risk management practices of life assurance firms and non‐life insurance firms. Design/methodology/approach – Through a comparative case study methodology, the study assesses the state of risk management in both life assurance companies and non‐life insurance firms to determine whether they exhibit different or similar risk management practices. The results of the survey were also analyzed and compared to the principles of good practices in financial risk management. Findings – The findings of the study revealed some differences and similarities in the risk management practices of life and non‐life insurance firms. Almost all the life companies have stated their risk appetite levels, which enable them to identify which risks to absorb and which ones to transfer. But non‐life insurance firms have not laid down their risk tolerance levels explicitly. The results further revealed that the industry lacks sufficient personnel with the requisite risk management skills and that the sector does not manage risks proactively, rather they do so in a reactive response to regulatory directives. Practical implications – Effective management of risks by insurers will increase the penetration of insurance in Ghana. Social implications – Risk management is a crucial issue, not only for the survival and profitability of the insurance industry, but also for the socio‐economic growth and development of the whole economy. As major risks underwriters, insurance companies need to adopt good practices or quality measures in the management of financial risk. This is important, more so, as the industry prepares to re‐position itself to underwrite the risks in the emerging oil and gas industry of Ghana. Originality/value – Research into financial risk management in the insurance industry from the Ghanaian perspective is rare. This study is therefore timely and its findings are invaluable for the efficient management of financial risk in the insurance industry.
Keywords: Life insurance; Risk management; Life assurance; Non‐life insurance; Ghana